Nightmare in Red: The McCarthy Era in Perspective - Fried, Richard M. (New York Oxford University Press, 1990)
Providing the most complete history of the rise and fall of the phenomenon known as McCarthyism, Nightmare in Red offers a riveting and comprehensive account of the many different people who became embroiled in the anti-communist fervor of mid-century America.
Keywords: Fiction